Chopin studies 2 - Rink, John; Samson, Jim (Cambridge Cambridge University Press, 1994)
Following the success of Chopin Studies, this second volume of essays contains the most recent Chopin research of twelve leading scholars. Three main themes are addressed: reception history, aesthetics and criticism, and performance studies. The essays explore Chopin as classical composer, as salon composer, as modernist, as "otherworldly," as androgyne, and define aspects of his musical language, including narrative structures, progressive tendencies and functional ambiguity.